Significado atribuidos por enfermeiros à assistênvcia que prestam a indivíduos em situação prisional - Apolinario, Fernando Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This study is about the significance of the assistance practices of the nurses who work in the penitentiary system of the Western region of the State of São Paulo, attending the incarcerated. The objective of this research is to characterize the units and identify the perceptions and the significances given to the nurses who work in the prison system by taking care of the prison inmates in closed system units. The methodological approach used to order and to analyse the obtained data by semistructured interviews was the Collective Subject Discourse. The “QualiQuantSoft’ software was used in this methodological process. The subjects of this research were the nurses that work at the above-mentioned service. With regard to the practice of nursing, it was possible to draw a picture marked by conflict imposed in hierarchical relationships, both formal and informal, that govern the routines at the prison units, especially the sectors of health and safety. Many difficulties for the accomplishing of the assistance were encountered: lack of a doctor, overcrowding, physical environments inappropriate for the attending of the subjects, insecurity, fear of working in the prison unit and, finally, the difficulty of making a reference and counter-reference according to the precept of integrality. Despite this difficulty, the nurse’s vision is one of a caregiver, with great meaning for his/her practices, because the feeling of empathy and the solidarity with those who are deprived of their liberty and are sick is quite evidenced. The nurse disregards the social condition of the detainee, identifying him as a human being in need of healthcare. The main ethical dilemmas experienced everyday by the nurses, according to reports, were related to the loss of autonomy in the nurses’ private competences, neglect in the care of the individual deprived of liberty in some municipalities and health units, and the impositions of assignments ...

Trata-se de estudo sobre o significado das práticas assistenciais dos Enfermeiros que atuam no Sistema Penitenciário na Região Oeste do Estado de São Paulo, em atendimento aos indivíduos em situação prisional. O objetivo da pesquisa é caracterizar as unidades e identificar as percepções e os significados atribuídos por enfermeiros que atuam no sistema prestando assistência aos presidiários nas unidades de sistema fechado. A abordagem metodológica para a ordenação e análise dos dados obtidos por meio de entrevistas semiestruturadas foi a do Discurso do Sujeito Coletivo (DSC). Neste processo metodológico utilizou-se o programa eletrônico “QualiQuantSoft”. Os sujeitos da pesquisa foram enfermeiros com atuação no referido serviço. Com relação à prática da assistência de enfermagem pode-se traçar um panorama marcado por situações de conflito impostas nas relações hierárquicas, formais e informais, que regulam as rotinas nas unidades prisionais, especialmente os setores de segurança e saúde. Foram apontadas muitas dificuldades para a realização da assistência, tais como: falta do médico, superlotação, ambiente físico inadequado ao atendimento, insegurança, medo de trabalhar nas unidades prisionais e, por fim, a dificuldade de realizar a referência e a contra-referência segundo o preceito da integralidade. Mesmo diante dessa dificuldade o olhar do enfermeiro é de cuidador, com grande significado para sua prática, pois o sentimento de empatia e de solidariedade ao privado de liberdade enfermo é bastante evidenciado. Com isso, o enfermeiro abstrai a condição social do detento, identificando-o como ser humano necessitado de cuidados à saúde. Os principais dilemas éticos vivenciados diariamente pelos enfermeiros, segundo relatos, foram os relacionados à perda de autonomia em competências privativas dos enfermeiros; ao descaso no atendimento do indivíduo privado de liberdade em alguns municipios ...
Keywords: Bioetica; Cuidados em enfermagem - Planejamento; Prisioneiros - Cuidado e tratamento; Enfermagem; Enfermeiros - Ética profissional; Nursing